Controle ativo de estruturas reticuladas utilizando atuadores de pilha de pzt - Joventino, Carlos Fernando [UNESP] (2015)
Flexible structures, for instance, trusses, are present in many industrial applications and have a great importance in the daily lives of people, either in a single telecommunications antenna, or either in more sophisticated and accurate devices, such as satellites orbiting in space. This work presents the design and the construction of a smart flexible structure. The control design of this structure was obtained through the implementation of an integral force controller. The controller design problem is solved by the root locus method, using a model identified experimentally by the system identification ERA / OKID method. Stack PZT (lead zirconate titanate) actuators were coupled in the structure with force sensors in order to obtain the active element responsible for vibration control of the structure. The problem of optimal sensors and actuators placement was solved using (Fraction Modal Deformation Energy technique, (FEDM)). The mathematical model used to calculate the placement of sensors and actuators was done by the finite element method. Analytical and experimental results for the problem of placement of sensors and actuators and the problem of active control are presented. The results showed that a pair of active elements in conjunction with the integral controller can be used to solve the problem of vibrations in flexible structures of truss type, considerably increasing their damping and hence attenuating the vibrations in the structure